Recent progress on hybrid reactive-extractive distillation for azeotropic separation: A short review - Kong, Zong Yang; Sunarso, Jaka; Yang, Ao (Frontiers in Chemical Engineering, 2022)
The reactive-extractive distillation (RED) has the advantages of combining the beneficial features of both reaction and separation processes. Relative to the conventional reactive or extractive distillation-based processes, the RED is also less energy intensive as it relies on the reaction heat produced for the subsequent separation process. Therefore, the application of RED for ternary azeotropic separation has become the subject of popular interest, as evident by the increasing number of publications since 2020. This review paper is the first that puts together, in a chronological manner, all the existing studies on the RED to date, starting from the initial three column reactive-extractive distillation (TCRED) to the most recent dividing wall reactive-extractive distillation (DW-RED), for ternary azeotropic separation, so that the rapid progress in this area is summarised and any existing gaps in these studies become easier to identify for future work. The last part of this review provides three potential areas for future work, i.e. analysis of the sustainability of RED, combination of different process intensification strategies to improve the energy efficiency and separation performance, and further exploration on the control studies for the RED.